Living Qur'an in the Tradition of Rokat Wajah in the Kramatagung Village Community, Probolinggo Regency - Luthviyah Romziana; Lumatul Himmah (Intiqad: Jurnal Agama dan Pendidikan Islam, 2023)
This study aims to describe the implementation of rokat in Kramatagung Village, Probolinggo Regency and to relate this tradition to the Koran and interpretation. The living Qur'an is scientific research carried out related to the Qur'an in a particular community, using a phenomenological descriptive method. The results of the study show that this culture is a native Javanese custom. The facial rokat tradition can be seen as a living Qur'anic phenomenon because of four things, first, the reading of the Mujiyat letter together; secondly, as a symbol of plea for salvation; third, as a medium of alms to neighbors; fourth, as a da'wah media based on local culture.